AB0962 Ankle Tendon Involvement in Patients with Spondylarthritis. (10th June 2014) - Vreju, F.; Chisalau, B.; Cojocaru Gofita, I.; Ivan, M.; Criveanu, C.; Florea, M.; Rosu, A.; Ciurea, P.
Abstract : Background: Management of spondylarthritis (SA) has evolved lately, in part due to new biologic therapies and part because of the new imaging techniques that can depict earlier involvement in joints and tendons. Objectives: to evaluate, by ultrasonography (US), the prevalence and type of the ankle tendons involvement in patients with spondylarthritis. Methods: Thirty-four patients with SA and ankle pain were included in the study (12 with ankylosing spondylitis - AS, 11 with psoriatic arthritis - PsA and 11 with reactive arthritis -ReA). Twenty healthy age-matched controls without inflammatory diseases were examined as well. The US evaluation included the anterior scan, the medial malleolar, lateral malleolar and posterior scan, for the evaluation of the following tendons: anterior tibialis tendon, extensor halux tendon and extensor common tendons, posterior tibialis tendon, flexor digitorum tendon and flexor hallux tendon, brevis and longus peroneous tendon and Achilles tendon. The presence of US findings indicative of tenosynovitis and tendon damage was investigated. Results: Tenosynovitis in at least one site, was statistically significant more frequent in patients with SA than in controls (58, 82% vs 10, 00%, p<0, 001). Between patients with SA, it was more frequent in PsA patients (72, 72%), followed by ReA patients (63, 63%), compared to those with AS (41, 66%). The most frequently involved tendon was tibialis posterior tendon in PsA and ReA patients and Achilles tendon in AS patients. We found partial or complete tears of the tendons in 3 patients from control group (15%) and 4 patients with SA (11, 76%). Conclusions: This study reveals the high frequency of ankle tendon involvement in patients with spondylarthritis and can guide the further assessment in the evaluation of those patients in daily practice. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5719